DAMPAK PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP KINERJA KEUANGAN DAN KINERJA PASAR - Muallifin, Ovi Rizki; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research discusses about the impact of the disclosure of sustainability report to the ROA, CR, DER, and Tobinâs Q. This research is meant to test the disclosure of sustainability report which has an influence to the financial performance and market performance. The samples are all company sectors which are listed in Indonesia Stock Exchange (IDX) in 2010-2014 periods. In this research, the sample collection technique has been determined and has been carried out by using purposive sampling and 9 companies have been selected as samples. This research has been done by using the MANOVA statistic technique. The result of this research shows that the sustainability report has an influence to the financial performance which has been measured by using CR, meanwhile the sustainability report does not have any influence to the financial performance which has been measured by using ROA and DER. The sustainability report does not have any influence to the market performance which has been measured by using Tobinâs Q.Keywords: Sustainability Report, ROA, CR, DER and Tobinâs Q.